ЎЗБЕКИСТОНДА ИШЛАБ ЧИҚАРИЛАДИГАН МЕВА ШАРБАТЛАРИ ҲАМДА МЕВАЛАРНИНГ АНАЛИЗИНИ ЎТКАЗИШ УСЛУБИЁТИ (Scientific journal of the Fergana State University, 2023)
The article presents and discusses the requirements of state standards of the Republic of Uzbekistan for fruit juices, as well as the results of determining the amount of ascorbic acid in various sorts of apples grown in the Fergana region